From Promise to Peril: Legal Uncertainty in Policyholder Protection in Mutual Fund Insurance Schemes Post Changes in Financial Sector Law in Indonesia - Maharani, Ferra Tiara (Program Studi Ilmu Hukum, Fakultas Hukum, Universitas Muslim Indonesia, 2025)
The Benefit Value Reduction Policy is a policy taken by AJB Bumiputera 1912 as a joint venture insurance. This policy was made with the aim of providing legal protection for the payment of policyholder claims and maintaining its form of business. This research discusses the legal protection of the implementation of AJB Bumiputera policyholder claims and the liability of AJB Bumiputera 1912 for its policies. Although there has been Law Number 4 of 2023 concerning Insurance Development and Strengthening of the Financial Sector, its application and enforcement still encounter various obstacles. Through the qualitative analysis method, this research reveals that legal protection to policyholders in the implementation of claims has not been fully achieved optimally. This is reflected in the fact that there are still complaints from policyholders regarding delays in claim disbursement, unclear information regarding benefit value deductions, and weak transparency in the PNM implementation process. and AJB Bumiputera has not fully carried out its obligations in the PNM policy implemented in relation to claim payments that were not made in a timely manner in 2023 and 2024.